Omics approaches and large-scale data analysis in ageing research 2 - Magalhães, João Pedro de (Henry Stewart Talks, 2017)
Data integration and network biology, Digital ageing atlas, Systems biology of ageing, GenAge as a tool, Pro- vs. anti- longevity C. elegans genes, Candidate gene prioritization, Systems biology of calorie restriction, GeneFriends co-expression map, DrugAge database of ageing-related drugs, Calorie restriction mimetics, Drug-gene interaction network